David Copperfield - Dickens, Charles, 1812-1870 ([Boston, Mass] : Thomson Heinle, 2005)
A boy grows to maturity in the affairs of the world and of the heart, surrounded by some of the author's most memorable characters. However, will David find happiness with the faithful Agnes Wickfield, whom he has known since childhood? Threatened by Uriah Heep, her father's clerk, the security of her own future is in question
Title from container
Keywords: Boys -- Fiction; England -- Fiction; Orphans -- Fiction; Young men -- Fiction; Stepfathers -- Fiction; Child labor -- Fiction